2020
DOI: 10.1101/2020.03.09.983155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who reviews for predatory journals? A study on reviewer characteristics

Abstract: Background: While the characteristics of scholars who publish in predatory journals are relatively wellunderstood, nothing is known about the scholars who review for these journals. We aimed to answer the following questions: Can we observe patterns of reviewer characteristics for scholars who review for predatory journals and for legitimate journals? Second, how are reviews for potentially predatory journals distributed globally? Methods:We matched random samples of 1,000 predatory journals and 1,000 legitima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…For that reason, we agree with Wang and Waltman's (2016) result that Web of Science performs better than Scopus in terms of accuracy. 26 Furthermore, this research has also revealed that predatory behavior conducts may occur also for journals included in Directory of Open Access Journals (1 case); journals which belong to Committee on Publication Ethics (7 cases) and for publishers that are not included in the Beall's List (6 journals).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…For that reason, we agree with Wang and Waltman's (2016) result that Web of Science performs better than Scopus in terms of accuracy. 26 Furthermore, this research has also revealed that predatory behavior conducts may occur also for journals included in Directory of Open Access Journals (1 case); journals which belong to Committee on Publication Ethics (7 cases) and for publishers that are not included in the Beall's List (6 journals).…”
Section: Discussionmentioning
confidence: 89%
“… See Gans and Shepherd (1994),Seidl et al (2005), Smith (2016), Ross-Hellauer (2017) for concerns in the peer-review process 26. Indeed the peer review process is one of the required conditions to be included in the Scopus and ISI -Web of Science databases.…”
mentioning
confidence: 99%
“…For an additional 6%, at least one respondent reported noticing something else that seemed odd. These results suggest that a fair number of questionable journals do organize some form of peer review (see also Severin et al, 2020), but the reviews are not necessarily actively used.…”
Section: Questionable Journals and Related Aspectsmentioning
confidence: 95%
“…These concerns became more tangible, as was highlighted by a study that identified over 6,000, from a total sample of 183,743, ‘predatory’ reviews (i.e., reviews of Cabell-blacklisted ‘predatory’ journals) on Publons. 16 …”
Section: How Has Peer Review Evolved Since the Acquisition?mentioning
confidence: 99%